Investigation of ICP‐MS/MS for total sulfur quantification in freshwater dissolved organic matter. Issue 6 (26th October 2021) - Kneer, Marissa L.; Lazarcik, James; Ginder‐Vogel, Matthew
Abstract: Sulfur‐containing functional groups in dissolved organic matter (DOM) interact with trace metals, which in turn affects trace metal mobility and bioavailability in aquatic environments. Typical methods for identification and quantification of sulfur in DOM are costly, complex, and time intensive. Triple quadrupole inductively coupled plasma tandem mass spectrometry (ICP‐MS/MS) is capable of part per billion–level sulfur quantification in environmental samples and is a more accessible analytical technique compared with other available methods. This study is the first published investigation of ICP‐MS/MS for the direct quantification of sulfur in freshwater DOM. Sulfur ( 32 S) detection occurs at a mass‐to‐charge ratio of 48 as 32 S 16 O + after removal of interferences and reaction with oxygen gas. We compare three commonly used DOM preparation methods to assess variability among replicate samples. Preparation of freshwater DOM samples by solid phase extraction followed by evaporation overnight and dissolution in 2% nitric acid results in the most accurate quantification of sulfur. Analysis of sulfur in Suwannee River Fulvic Acid standard serves as method validation, measuring a carbon‐normalized sulfur concentration that is ∼20% higher than previously reported methods. We apply the ICP‐MS/MS analysis method to determine sulfur concentrations in DOM from nine lakes in the northern Midwest. Carbon‐normalized sulfur concentrations in the selected lakes are in general agreement with previously reported percentages of sulfur‐containing formulas in DOM found by Fourier transform–ion cyclotron resonance–mass spectroscopy. Core Ideas: ICP‐MS/MS accurately measures sulfur in varied freshwater dissolved organic matter. This method is suitable for S quantification down to 0.2 ng g –1 S. Drying dissolved organic matter extracts overnight provides consistent S detection. Carbon‐normalized S concentrations agree with previously published results.